Penerapan Prinsip Responsibility Perusahaan Perhotelan Provinsi Bali dalam Pemberian Cuti Tak Berbayar (Unpaid Leave) Pasca Pandemi Covid-19 - Zalza Puti Kamila; Yeti Sumiyati (Bandung Conference Series: Law Studies, 2023)
Abstract. The principle of responsibility is part of the principles of Good Corporate Governance that must be applied by the company as a form of compliance with laws and regulations in managing company activities. The principle of responsibility makes the company have the obligation to provide humanitarianly decent wages to its employees in accordance with what has been stated in the Employment Agreement and Laws and Regulations. The principle of responsibility for the company is explained through Law Number 40 of 2007 concerning Limited Liability Companies, Law Number 13 of 2003 concerning Manpower, and Law Number 11 of 2020 concerning Job Creation. In circumstances where the company experiences financial difficulties due to the Covid-19 pandemic so that it is unable to provide wages in accordance with the agreement, the company can carry out wage deductions through the provision of unpaid leave by fulfilling the provisions according to Government Regulation Number 36 of 2021 concerning Wages and Decree of the Minister of Manpower Number 104 of 2021 concerning Guidelines for the Implementation of Employment Relations During the Corona Virus Disease Pandemic 2019. But in practice, PT. "X", which is a hotel company in the province of Bali, still enforces the provision of unpaid leave during the post-Covid-19 pandemic. This research uses normative juridical research methods, namely literature law research conducted by examining literature materials and field data obtained through interviews. The results showed that the provision of unpaid leave by PT. "X" does not meet the provisions related to the application of the principle of responsibility in terms of providing a decent wage based on the agreements in the employment agreement and collective agreement. Abstrak. Prinsip responsibility merupakan bagian dari prinsip Good Corporate Governance yang wajib diterapkan oleh perusahaan sebagai bentuk ketaatan terhadap peraturan perundang-undangan dalam mengelola aktivitas perusahaan. Prinsip responsibility membuat perusahaan memiliki kewajiban untuk memberikan upah yang layak secara kemanusiaan kepada para karyawannya sesuai dengan yang telah disebutkan dalam Perjanjian Kerja serta Peraturan Perundang-Undangan. Prinsip responsibility bagi perusahaan tersebut dijelaskan melalui Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas, Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan, dan Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja. Dalam keadaan dimana perusahaan mengalami kesulitan finansial akibat pandemi Covid-19 sehingga tidak mampu memberikan upah sesuai dengan kesepakatan, maka perusahaan dapat melaksanakan pemotongan upah melalui pemberian cuti tak berbayar dengan memenuhi ketentuan menurut Peraturan Pemerintah Nomor 36 Tahun 2021 tentang Pengupahan dan Keputusan Menteri Ketenagakerjaan Nomor 104 Tahun 2021 tentang Pedoman Pelaksanaan Hubungan Kerja Selama Masa Pandemi Corona Virus Disease 2019. Namun dalam praktiknya, PT. “X” yang merupakan perusahaan perhotelan di provinsi Bali masih tetap memberlakukan pemberian cuti tak berbayar tersebut pada masa pasca pandemi Covid-19. Penelitian ini menggunakan metode penelitian yuridis normatif, yakni penelitian hukum kepustakaan yang dilakukan dengan cara meneliti bahan kepustakaan serta data lapangan yang didapat melalui wawancara. Hasil penelitian menunjukkan bahwa pemberian cuti tak berbayar oleh PT. “X” tidak memenuhi ketentuan terkait penerapan prinsip responsibility dalam hal memberikan upah yang layak berdasarkan kepada kesepakatan dalam perjanjian kerja dan perjanjian bersama.